Insect Fauna of Lucerne (MEDICAGO Sativa Linn.) Chop in Desert Belt of Rajasthan - Parihar, D R; Vir, Satya (Annals of Arid Zone, 2016)
During surveys, 42 insects on lucerne crop were collected and identified of which 22 constituted as new records. Out of these, fi. e viz. Ilypera postica, Utethesia lotrix. Theriouphit trifolli maculata, Rhopalosiphllm maldis and Aphis craccivora were found to cause serious damage to crop.Four hymenopterans parasites and 8 species of predators were also recorded.